Effectiveness of Online and Traditional Class: A Comparative Analysis - Micabalo, Kingie G.; Cano, Jesszon B.; Navarro, June Ace P.; Atillo, Lucilito A.; Montilla, Ryan D. (Asian Journal of Electrical Sciences, 2020)
Educating and learning modalities in virtual and customary classes can be best seen as a marker of proficiency and college adequacy. The examination decides the adequacy of online and traditional classes to the College of Business and Accountancy. The respondents were the 208 understudies from the University of Cebu Lapu and Mandaue utilizing the descriptive - comparative research method on a snowball sampling. Frequency and simple percentage, Mean, Chi- Square Test of Independence and Independent Samples T-test were utilized, to sum up, separate, and unwind the information assembled. The findings revealed that there is statistically significant difference on the level of effectiveness between online and traditional class. The understudies perceived online class as moderately effective while perceiving traditional class as highly effective. Moreover, it revealed that there is a statistically significant correlation on the respondents gender, course and year level on the level of perception either by traditional or online classes. The study concludes that Online and Traditional modalities of educating and learning extraordinarily assume an essential function on an understudy's useful term in school. However, refinement of approaches to these modalities is very important to portray student-teacher resiliency at any given situation.